Modulation of Platelet Activation In Vitro by Thrombopoietin - Kojima, Hiroshi; Hamazaki, Yoko; Nagata, Yuka; Todokoro, Kazuo; Nagasawa, Toshiro; Abe, Tsukasa (Thrombosis and Haemostasis, 1995)
Effect of human recombinant thrombopoietin (TPO) on platelet activation in vitro was studied. Although TPO by itself did not cause platelet aggregation, it upregulated ADP-induced aggregation, especially the second wave of aggregation. This effect was dose-dependent for up to 5 ng/ml of TPO. When platelets were activated by epinephrine, collagen, or α-thrombin, similar effect was observed. However, TPO did not affect A23187- or PMA-induced aggregation, suggesting that TPO may have modulated the signal transduction pathway upstream of inositol 1,4,5-trisphosphate and diacylglycerol production. TPO also upregulated thrombin-induced α-granule secretion. To clarify the involvement of protein tyrosine phosphorylation, platelets were activated by TPO and/or suboptimal concentration of ADP, then tyrosine phosphorylation was detected by immunoblot analysis, using anti-phosphotyrosine monoclonal antibody. TPO by itself caused significant tyrosine phosphorylation of 146,130,122,108, 97,94, and 88 kDa proteins. Further, by using antibodies against signal transduction molecules for immunoprecipitation, we observed the significant tyrosine phosphorylation in Jak2 and Tyk2 molecules after TPO-stimulation. The results of the present experiment clearly indicate that TPO directly activated platelets and modulated intracellular signal transduction pathway.